Barriers and Enablers to Inclusive Education in Mauritius: Perceptions of Secondary School Educational Practitioners - Nazia Abdoula-Dhuny (Sustainable Programs to Reduce Educational and Avocational Disadvantages (SPREAD), 2021)
Advocated as an educational philosophy to tackle exclusion, inclusive education (IE) is now a worldwide trend. Despite the well-acknowledged benefits of inclusion, educational practitioners have several difficulties which act as significant setbacks in operationalising inclusion in practice. Given its novelty in Mauritius, IE implementation is not fully understood. The purpose of the study was to explore the perceptions of secondary school educational practitioners on certain aspects of inclusive education, namely the academic profile of students with special education needs encountered by secondary school educators and rectors, the difficulties faced when dealing with them, and the barriers and enablers to inclusive education. It involved a quantitative descriptive research design. Data were collected from 588 secondary educators and 42 rectors using a specifically designed questionnaire. Following the analysis of data, respondents confirmed the presence of children with special education needs in their classrooms. While respondents indicated that the majority of students with special education needs had an academic profile of the same level of age-matched peers, they reported difficulties encountered with these learners in terms of deficits in attention, participation and behavioural problems. The main barriers identified were the lack of training in special education and the lack of proper infrastructure. Findings revealed training and knowledge in special education, the availability of proper infrastructure, support in terms of teaching aids, specialised equipment and teaching assistants as the main enabling factors. Training is therefore recommended to build competency of educators and rectors in inclusive practices. Appropriate infrastructure and support in terms of educational materials and support personnel should also be provided.